1995
DOI: 10.1099/0022-1317-76-12-2979
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation of peripheral T cells in chickens infected with Marek's disease virus: involvement in immunosuppression

Abstract: Marek's disease virus (MDV) causes T cell immunosuppression in chickens during latent infection. Morphological changes specific to apoptosis were demonstrated in peripheral blood mononuclear cells (PBMC) of MDV-infected chickens at 2-3 weeks post-inoculation (p,i.). Analysis of DNA fragmentation in T cell subsets in the peripheral blood revealed that CD4 + T cells but not CD8 + T cells underwent apoptosis after MDV infection. The proportion of CD4 + T cells, but not that of CD8 + T cells, in the peripheral b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
1

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 36 publications
0
30
1
Order By: Relevance
“…Total cellular RNAs (5 g each) extracted with Trizol (Life Technologies, Inc.) were separated on a 1% agarose gel containing 1% formamide in MOPS buffer, and transferred to a nylon membrane (Biodyne; Pall, East Hills, NY). Hybridization was performed as described previously (51).…”
Section: Methodsmentioning
confidence: 99%
“…Total cellular RNAs (5 g each) extracted with Trizol (Life Technologies, Inc.) were separated on a 1% agarose gel containing 1% formamide in MOPS buffer, and transferred to a nylon membrane (Biodyne; Pall, East Hills, NY). Hybridization was performed as described previously (51).…”
Section: Methodsmentioning
confidence: 99%
“…Cellular immune response can also be enhanced by ionophores addition (Munir et al, 2009). Prebiotics and ionophores used to prevent coccidiosis can indirectly stimulate the immunity in post vaccination of poultry against certain immunosuppressive diseases affecting the lymphoid organs or against infections predisposing to coccidiosis such as Marek's disease which affects the T cell response (Morimura et al, 1995). Thus, the MOS enhances the immune response by increasing the antibody titer during vaccination against infectious bursal disease (Oliviera et al, 2009) and Newcastle disease (Gomez-Verduzco et al, 2009a;Oliviera et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, if the more highly virulent MDV strains caused greater rates of apoptotic cell death of effector T-cells, then there would be a greater degree of immunodepression which could lead to more tumours. Morimura et al (1995Morimura et al ( , 1996 have reported that thymic atrophy in chickens infected with the vv MDV strain Md5 resulted from apoptosis of immature CD4 + CD8 + thymocytes, and that CD4 + , but not CD8 + T-cells in the peripheral blood underwent apoptotic cell death at 2 to 3 weeks post-infection. They also observed that CD8 expression is down-regulated after MDV infection, and therefore concluded that both apoptosis and CD8 down-regulation may contribute to immunodepression associated with MDV infection.…”
Section: Differing Affinities For Virus Receptorsmentioning
confidence: 99%
“…However, other mechanisms also are involved; these are now known to include apoptosis, "down-regulation of CD8 and potential immunodepressive effects of MDV gene products. Morimura et al (1995Morimura et al ( , 1996 demonstrated apoptotic changes in peripheral blood lymphocytes (PBL) at 2 to 3 weeks post-infection in MDV-infected chickens. At about 16 d.p.i., CD4 + , but not CD8 + , cells underwent a transient expansion and then were markedly reduced in number, apparently by apoptosis.…”
Section: Escape From Immunosurveillancementioning
confidence: 99%